2022
DOI: 10.3389/fphar.2022.881042
|View full text |Cite
|
Sign up to set email alerts
|

Worenine Prevents Solar Ultraviolet–Induced Sunburn by Inhibiting JNK2

Abstract: Excessive solar ultraviolet (SUV) radiation often causes dermatitis, photoaging, and even skin cancer. In the pathological processes of SUV-induced sunburn, JNK is activated by phosphorylation, and it in turn phosphorylates its downstream transcription factors, such as ATF2 and c-jun. The transcription factors further regulate the expression of pro-inflammatory genes, such as IL-6 and TNF-α, which ultimately leads to dermatitis. Therefore, inhibiting JNK may be a strategy to prevent dermatitis. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Worenine is one of the main bioactive components extracted from the dried rhizome of Coptis chinensis 11 . Our previous paper found that worenine prevented Solar UltraViolet‐induced sunburn by inhibiting JNK2 signalling 12 . In this work, the anti‐psoriasis effect of worenine by inhibiting TOPK was determined in cell model and animal model.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Worenine is one of the main bioactive components extracted from the dried rhizome of Coptis chinensis 11 . Our previous paper found that worenine prevented Solar UltraViolet‐induced sunburn by inhibiting JNK2 signalling 12 . In this work, the anti‐psoriasis effect of worenine by inhibiting TOPK was determined in cell model and animal model.…”
Section: Introductionmentioning
confidence: 87%
“…ELISA was performed as previously described 12 . ELISAs were performed using ELISA kits according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations